THE TEACHERS' CLINIC. - Kaulback, Frank S.; Crum, William F.; Field, Ernest R.; Dunn, Clarence L.; Boyd, Orton W. (The Accounting Review, 1956)
Abstract One advantage of taking a CPA Review course from an experienced instructor is that it provides the inexperienced candidate with an over-view of the types of questions and subjects most apt to be touched upon. The candidate needs to acquire perspective. Many students taking the examination immediately upon finishing their university training, do not know whether three hours spent in a review of process costs will be as valuable as three hours' review of the break even point or perhaps the subject of joint ventures. A thorough application of the principles of commercial law is useful in recognizing accounting consequences of legal documents such as contracts for the sale of merchandise, bills of lading, underwriting contracts, stock option agreements, pension plans, and employee profit-sharing plans. Careful attention must be directed to outlining the special rights, privileges, and priorities of various classes of common and preferred stock. Restrictions on dividends resulting from long-term bond indentures must be properly explained. These are just a few of the items encountered.